The Effect of Owner’s Characteristics through Innovation on the MSMEs Performance - Ririn Wulandari; Wei-Loon Koe (Universitas Prasetiya Mulya, 2022)
This study aims to analyze the influence of the characteristics of MSME owners on their performance through innovation in Indonesia and Malaysia. Structural Equation Modeling (SEM) was used to analyze the data, with the Smart-PLS program. The population in this study was Micro, Small, and Medium Enterprises from various types of businesses. The number of respondents was 225 from Indonesia and Malaysia. The sampling technique used was stratified judgment sampling. Questionnaire in the form of Google Forms and distributed via WhatsApp, Facebook, and Instagram. The study results show that innovation affects the performance of MSMEs in Indonesia and Malaysia. In Indonesia, owner characteristics influence innovation but do not affect performance. With the characteristics they have, MSME owners can improve their performance through the creation of innovations. However, this is not the case in Malaysia.